Parental involvement in remote learning of children with academic difficulties during the pandemic - Kanapi, Ma. Erika Luis
The education sector was among the industries that were greatly affected and changed drastically by the COVID-19 pandemic. It closed down physical schools which led to a sudden shift to remote learning. Despite considerable efforts by the government to provide the necessary tools and exemplary teachers to offer quality education to all students during the pandemic, few attempts were made for children with academic difficulties. Since these students were bound to stay at home, the responsibility for teaching and learning was placed on the parents and other family members. Thus, the purpose of this case study is to describe the roles, experiences, and challenges of the nine parents with academic difficulties during the sudden shift to remote learning. A qualitative approach was used for data collection and analysis. Semi-structures interview, class observation, and focus group discussions were conducted via videoconferencing to gather data during the lockdown. The findings of this study revealed five primary types of parental involvement within this setting: (1) providing for their child's needs, (2) organizing space and time (3) motivating and monitoring the child's behavior (4) instructing technology and lesson-related problems (5) and adapting the lessons. This study also suggests relevant implications and recommendations for educators and policymakers.